1986
DOI: 10.1111/j.1439-037x.1986.tb00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the Sink/Source Relationships in Bread Wheat and its Influence on Grain Yield and Grain Protein Content*

Abstract: Artificial manipulation of sink and source was carried out in several bread wheat varieties in order to study the variations in the pattern of storage products accumulation in the grain. In a first experiment, partial ablation of the laminae did not cause any significant variation in the yield components, while total elimination of the laminae resulted in a decreased fertility of the spikelets and in a lower kernel weight. The protein content of grain turned out to be a function of the amount of vegetative org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0
2

Year Published

1989
1989
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 15 publications
(10 reference statements)
1
17
0
2
Order By: Relevance
“…Therefore, the common explanation that a higher number of grains m −2 reduces assimilate availability per individual grain may be true if source limitations occur during grain filling. Yet, wheat, particularly under optimum conditions, has been reported to be sink limited (Borojevic, 1979; Thorne et al, 1979; Borghi et al, 1986; Bindraban, 1997). In the case of barley, TKW is higher than in wheat even when number of grains m −2 is the same and the duration of grain filling is shorter (Richards, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the common explanation that a higher number of grains m −2 reduces assimilate availability per individual grain may be true if source limitations occur during grain filling. Yet, wheat, particularly under optimum conditions, has been reported to be sink limited (Borojevic, 1979; Thorne et al, 1979; Borghi et al, 1986; Bindraban, 1997). In the case of barley, TKW is higher than in wheat even when number of grains m −2 is the same and the duration of grain filling is shorter (Richards, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…2b). The findings that hybrid wheats show positive correlations between protein content and total biomass (Corbellini and Borghi 1985;Borghi et al 1986) and produce large amounts of dry .t-irt'-i"t-)it'\"r1t'l"rf l"r"lir'1i"r""",F .fr*t1i"tl?",'.'."t-">l','"r"$r",1"r";'ir. "",F PERFoRMANCT (Z) baking characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…The number of grains m 2 is more associated with grain yield than individual grain weight under different environmental conditions and cultivars (Fischer, 1985;Caldiz & Sarand6n, 1988;Slafer & Andrade, 1989a& 1991Savin & Slafer, 1991), because wheat grain yield is normally sink-limited during the grain filling period (Perez & MartinezCarrasco, 1985;Borghi et al, 1986;Savin & Slafer, 1991); although some source limitation has recently been suggested (Grabau et al, 1990;Ma et al, 1990).…”
Section: Introductionmentioning
confidence: 99%